Broadband coaxial holder with continuous‐conductor used for shielding effectiveness of materials against electromagnetic pulse. Issue 8 (1st April 2013) - Chen, X.; Chen, Y.G.; Wei, M.; Cui, M.
Abstract : To accurately evaluate the shielding effectiveness of materials against the electromagnetic pulse, a coaxial holder with a continuous‐conductor which uses a step transition has been developed. The particle swarm optimisation solver of CST Microwave Studio is used to design the fixed support of the coaxial holder. The cutoff frequency of the coaxial holder is up to 10 GHz with the return loss of less than − 20 dB in the frequency range of 10 MHz–8 GHz. Silver‐plated fabric and blended fabric with stainless steel fibre and polyester fibre have been tested in frequency‐domain and time‐domain, and these insertion loss and time‐domain waveforms have been compared with the 1.6GHz previous coaxial holder. Load specimens required by the broadband coaxial holder are smaller than the previous coaxial holder, while the error introduced by the broadband coaxial holder is much smaller.